Investigating the effect of solvent boiling temperature on the active layer morphology of diffusive bilayer solar cells. (24th December 2015) - Vohra, Varun; Dörling, Bernhard; Higashimine, Koichi; Murata, Hideyuki
Abstract: Using chlorobenzene as a base solvent for the deposition of the poly(3-hexylthiophene-2, 5-diyl) (P3HT) layer in P3HT:phenyl-C61 -butyric acid methyl ester diffusive bilayer solar cells, we investigate the effect of adding of small amounts of high-boiling-point solvents with similar chemical structures on the resulting active layer morphologies. The results demonstrate that the crystallinity of the P3HT films as well as the vertical donor–acceptor gradient in the active layer can be tuned by this approach. The use of high-boiling-point solvents improved all photovoltaic parameters and resulted in a 32% increase in power conversion efficiency.